Ethic Analysis of Government Goods and Services Procurement Officials in Indonesia - Ulinata, Ulinata (Formosa Journal of Applied Sciences, 2024)
In carrying out the process of procuring goods and services, especially in the field of architecture, officials are obliged to prioritize ethics so that the implementation is professional, with integrity and accountability so that no irregularities occur. This research aims to analyze how ethics is applied in the implementation of government procurement of goods and services in Indonesia. This research uses a descriptive analysis method by collecting literature studies, observations are then analyzed. The results show that officials involved in providing goods and services are required to apply ethics and have a professional spirit, not influence each other, avoid conflicts of interest, take preventive actions that result in waste, not abuse authority and accept gratification, accept duties and responsibilities well.